Normative Review Of Indigenous Community Rights In Mining Areas - Dhea Meila Fitriani (Universitas Negeri Gorontalo, 2021)
This study aims to determine the rights of indigenous peoples in mining areas. The research method is a normative research method using a descriptive approach and qualitative analysis techniques. The results of this study show that the position of the rights and obligations of indigenous peoples in the mining world is still far from clear and has not been able to provide clear and unequivocal protection in the Mineral and Coal Law. Article 18B (2) of the 1945 Constitution, as one of the constitutional foundations of indigenous peoples, stipulates declarative recognition that the State recognizes and respects the existence and rights of indigenous peoples. However, this recognition sets limits or requirements for a community to be recognized as a customary law community. The Government must have full responsibility to protect and provide avenues and forums for indigenous peoples to maintain their rights in maintaining their existence.